2005
DOI: 10.1099/vir.0.80675-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of porcine reproductive and respiratory syndrome virus attachment and internalization: distinctive roles for heparan sulphate and sialoadhesin

Abstract: Heparan sulphate and sialoadhesin were previously identified on porcine macrophages as receptors for porcine reproductive and respiratory syndrome virus (PRRSV). In this study, the exact role and cooperation of heparan sulphate and sialoadhesin during PRRSV attachment and internalization was analysed. It was observed that both heparan sulphate and sialoadhesin mediate PRRSV attachment and that only these two receptors are involved in attachment. Analysis of attachment kinetics of PRRSV to macrophages revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
81
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 18 publications
3
81
0
1
Order By: Relevance
“…There are some neutralizing epitopes known on GP5 and GP4 [39,48,66] and there are possibly also neutralizing epitopes on GP3 [5], but it is not known if other important epitopes exist and which neutralizing epitopes are most important. Previous results from our lab showed that PRRSV neutralizing antibodies block infection by preventing the interaction of PRRSV with the internalization receptor sialoadhesin (Sn) on the target cells, macrophages [15,16,60,61]. This indicates that neutralizing antibodies are directed to the viral epitopes that are involved in the attachment to the PRRSV receptors and internalization into the macrophage [15].…”
Section: Introductionmentioning
confidence: 96%
“…There are some neutralizing epitopes known on GP5 and GP4 [39,48,66] and there are possibly also neutralizing epitopes on GP3 [5], but it is not known if other important epitopes exist and which neutralizing epitopes are most important. Previous results from our lab showed that PRRSV neutralizing antibodies block infection by preventing the interaction of PRRSV with the internalization receptor sialoadhesin (Sn) on the target cells, macrophages [15,16,60,61]. This indicates that neutralizing antibodies are directed to the viral epitopes that are involved in the attachment to the PRRSV receptors and internalization into the macrophage [15].…”
Section: Introductionmentioning
confidence: 96%
“…The glycosaminoglycan heparan sulphate is a PRRSV receptor that is involved in PRRSV attachment via its interaction with structural matrix protein and the matrixglycoprotein 5 complex [13,43]. Sialoadhesin, a sialic acid binding immunoglobulin-like lectin [11], also mediates PRRSV attachment to macrophages [15,44]. Initial attachment of PRRSV to macrophages is mediated mainly via an interaction with heparan sulphate, followed by a gradual increase in interaction with sialoadhesin [15].…”
Section: Introductionmentioning
confidence: 99%
“…Sialoadhesin, a sialic acid binding immunoglobulin-like lectin [11], also mediates PRRSV attachment to macrophages [15,44]. Initial attachment of PRRSV to macrophages is mediated mainly via an interaction with heparan sulphate, followed by a gradual increase in interaction with sialoadhesin [15]. Sialoadhesin is the PRRSV internalization receptor [15,19,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sialoadhesin (Sn) was identified as an essential PRRSV receptor that mediates both attachment and internalization on macrophages (5-7, 9, 26). Although Sn was shown to be essential for infection of macrophages, other, unidentified, factors are essential for productive infection, since expression of Sn in PRRSV nonpermissive cells, such as PK-15 and CHO K1 cells, allows virus internalization but no virus uncoating, genome release, or production of infectious virus (5,26). Other putative PRRSV receptors have been described.…”
mentioning
confidence: 99%